PENGEMBANGAN PERENCANAAN PENDIDIKAN ISLAM DI RUMAH TAHFIZ YATIM-PIATU LASI: STUDI KASUS PADA IMPLEMENTASI PROGRAM EDUKASI HOLISTIK - Yusra; Iswantir M (JOURNAL SAINS STUDENT RESEARCH, 2023)
This journal discusses efforts to develop Islamic education planning in tahfiz homes that serve orphans. The research was conducted by conducting a case study on a tahfiz house that has implemented a holistic education program. The research method involved observation, interviews and documentation analysis to describe the implemented Islamic education planning. The results show that the development of educational planning in an orphanage tahfiz house contributes positively to the holistic development of learners. This educational planning involves religious, academic, social, and practical skills aspects. The existence of an integrated curriculum that focuses on the formation of Islamic character and personality characterizes the educational planning in this tahfiz house. This article also discusses the challenges faced in developing Islamic education planning in tahfiz homes for orphans. The existence of limited resources, both financial and teaching staff, is a factor that needs to be considered in designing effective and sustainable educational planning. Thus, this journal provides insight into the importance of developing holistic Islamic education planning in orphanages as an effort to improve the quality of education and form a noble generation in accordance with Islamic values. This study can provide input for other institutions.